Association between normal weight obesity and lipids profile in Slovak women aged 38 to 59 years - Ferjančeková, Daniela; Švábová, Petra; Hozáková, Alexandra; Sulis, Simona (Anthropological Review, 2024)
Obesity and its associated health problems are an issue, especially when weight gain is not outwardly visible. Individuals with the same Body Mass Index (BMI) may differ in body fat percentage and may unknowingly suffer from normal weight obesity (NWO). Middle-aged women are at high risk if their body composition changes due to factors such as age, health status or reproductive history. This study investigated the relationship between NWO and lipid profile in middle-aged women. A sample of 122 women aged 38 to 59 years (47.17 ± 5.24) from Slovakia participated in this study. Using a questionnaire, participants answered questions about lifestyle, health background, sociodemographic classification, reproductive and menstrual history. The anthropometric parameters were determined using standard methods. Body composition was measured using a bioelectrical impedance analyzer. Biochemical parameters were determined from morning blood samples. Blood pressure was assessed in a sitting position using a digital sphygmomanometer. The primary aim of this study was to assess the differences in lipid profiles between NOW women and normal weight-lean (NWL) women. Our results showed statistically significantly higher values of uric acid in the women with NWO compared to NWL women (237.39 ± 54.11 μmol/l vs. 213.02 ± 52.64 μmol/l; p = 0.009). Moreover, significant differences were noted between NWO women and NWL women in body height, body weight, waist and hip circumference, WHR, BMI and fat mass (%, p < 0.05). Other biochemical variables showed no statistically significant differences between the study groups of women. Elevated uric acid levels in women diagnosed with NWO may serve as an indication of metabolic imbalance associated with undetected obesity. These results underscore the importance of implementing early detection and intervention methods for NWO to prevent related health issues. Further research is necessary to investigate the underlying factors contributing to these connections and evaluate the efficacy of customized interventions.